The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2013
DOI: 10.1186/2251-6581-12-50
|View full text |Cite
|
Sign up to set email alerts
|

Relation between carotid intima media thickness and oxidative stress markers in type 1 diabetic children and adolescents

Abstract: BackgroundCarotid intima media thickness (CIMT) is a non invasive marker of subclinical atherosclerosis. Hyperglycemia, oxidatively modified atherogenic lipoproteins and advanced glycation end products are linked to increased oxidative stress in diabetes. We aimed to find out the relation between carotid intima media thickness in type 1 diabetic children and adolescents and plasma nitric oxide and total antioxidant capacity levels as markers of oxidative stress.MethodsThis study included 50 children and adoles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
10
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 53 publications
(53 reference statements)
4
10
1
Order By: Relevance
“…In these studies, the duration of the disease was shorter than that in our study, which might explain our findings. Furthermore, we found no association between CIMT and glycemic control measured by HbA1c, as reported in other studies (19,20). Our results are similar to those of another study in a cohort of 603 patients with type 1 DM followed up for 10 years, which found that a better glycemic control was unable to predict the occurrence of coronary artery disease (CAD), in contrast to insulin resistance measured by eGDR, which emerged as a predictor of CAD endpoints (27).…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…In these studies, the duration of the disease was shorter than that in our study, which might explain our findings. Furthermore, we found no association between CIMT and glycemic control measured by HbA1c, as reported in other studies (19,20). Our results are similar to those of another study in a cohort of 603 patients with type 1 DM followed up for 10 years, which found that a better glycemic control was unable to predict the occurrence of coronary artery disease (CAD), in contrast to insulin resistance measured by eGDR, which emerged as a predictor of CAD endpoints (27).…”
Section: Discussionsupporting
confidence: 69%
“…A study in 150 patients with longstanding type 1 DM has found a lower prevalence of subclinical atherosclerosis (18). In contrast, other studies have reported increased CIMT in children and adolescents with type 1 DM, demonstrating that the atherosclerotic process may start at a young age in these patients (19,20). Our results provide further evidence of the importance of screening for subclinical CVD in women with type 1 DM.…”
Section: Resultssupporting
confidence: 52%
See 2 more Smart Citations
“…Our data revealed that the total antioxidant activity (ORAC) decreased in the plasma of children with diabetes in favor of an oxidative stress in such patients. These results are in agreement with previous studies (El Samahy et al, 2013;Varvarovská et al, 2003).…”
Section: Discussionsupporting
confidence: 83%